Regulation of sarcomagenesis by the empty spiracles homeobox genes EMX1 and EMX2 - Amancio Carnero; Manuel P. Jiménez-García; Daniel Otero-Albiol; Antonio Lucena-Cacace (Cell Death & Disease, 2021)
The EMX (Empty Spiracles Homeobox) genes EMX1 and EMX2 are two homeodomain gene members of the EMX family of transcription factors involved in the regulation of various biological processes, such as cell proliferation, migration, and differentiation, during brain development and neural crest migration. They play a role in the specification of positional identity, the proliferation of neural stem cells, and the differentiation of certain neuronal cell phenotypes. In general, they act as transcription factors in early embryogenesis and neuroembryogenesis from metazoans to higher vertebrates. The EMX1 and EMX2 ’s potential as tumor suppressor genes has been suggested in some cancers. Our work showed that EMX1 / EMX2 act as tumor suppressors in sarcomas by repressing the activity of stem cell regulatory genes ( OCT4 , SOX2 , KLF4 , MYC , NANOG , NES , and PROM1 ). EMX protein downregulation, therefore, induced the malignance and stemness of cells both in vitro and in vivo. In murine knockout (KO) models lacking Emx genes, 3MC-induced sarcomas were more aggressive and infiltrative, had a greater capacity for tumor self-renewal, and had higher stem cell gene expression and nestin expression than those in wild-type models. These results showing that EMX genes acted as stemness regulators were reproduced in different subtypes of sarcoma. Therefore, it is possible that the EMX genes could have a generalized behavior regulating proliferation of neural crest-derived progenitors. Together, these results indicate that the EMX1 and EMX2 genes negatively regulate these tumor-altering populations or cancer stem cells, acting as tumor suppressors in sarcoma.